Caspian Sea as a continuation of the history of determining the border of the Republic of Kazakhstan - Baishov, B.B.; Alikulova, N.S.; Demeuova, N.K.; Orazaeva, Zh.Zh. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article examines the aspirations of our sovereign state to strengthen its foreign policy since 1991 and the process of demarcation of the border, maintaining good neighborly relations with neighboring countries. One of the most important achievements in solving the problem was the decision in August 2018 to demarcate the Caspian Sea border, which is of strategic importance in strengthening the state border of Kazakhstan, preserving the territorial integrity and independence of the country, ensuring national security. The main purpose of our scientific article is to reveal the historical significance of the actions taken on the Caspian Sea, the latest milestone in the actions of the Republic of Kazakhstan to strengthen the country's borders. The scientific novelty of the work is a comprehensive, concise analysis of the measures taken in the Republic of Kazakhstan to clarify the borders of the country since 1991 and the optimal use of the existing experience of Kazakh diplomacy in defining the status of the Caspian Sea. We believe that some of the results of our research can be applied to the study of this topic.
Каспий теңізі ― Қазақстан Республикасының шекарасын айқындау тарихының жалғасы ретінде
Каспийское море как продолжение истории определения границ Республики Казахстан
Keywords: Caspian Sea; Convention; border; delimitation; demarcation; memorandum; diplomacy; summit; The Great Silk Way; Kazakhstan-2050